2019
DOI: 10.2147/prbm.s202127
|View full text |Cite
|
Sign up to set email alerts
|

<p>The protective effect of psychological <em>suzhi</em> on the relationship between school climate and alcohol use among Chinese adolescents</p>

Abstract: Background: There issome research on school climate impact on adolescent alcohol use in the Western social context; however, there is no research on school climate impact on adolescent alcohol use in China. This study aimed to explore the effect of school climate on Chinese adolescents’ alcohol use, and the moderating role of psychological suzhi between them. Methods : A total of 801 adolescents (45.8% boys, 14.96±1.66 years) completed self-reports on school climate, psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
8
0
4
Order By: Relevance
“…The cognitive quality, which is shown through cognitive processing (Wang, 2013), determines the degree to which individuals perceive the school climate, that is, under the positive perceived school climate, negative events such as bullying and victimization will have a lower negative impact on psychological suzhi. The positive effect of psychological suzhi on suicidal ideation will be enhanced (Liu et al, 2019). Therefore, we proposed the following hypothesis (H4): perceived school climate is also a moderated factor in the mediating (psychological suzhi) first half of pathway.…”
Section: The Moderating Role Of Perceived School Climatementioning
confidence: 97%
See 2 more Smart Citations
“…The cognitive quality, which is shown through cognitive processing (Wang, 2013), determines the degree to which individuals perceive the school climate, that is, under the positive perceived school climate, negative events such as bullying and victimization will have a lower negative impact on psychological suzhi. The positive effect of psychological suzhi on suicidal ideation will be enhanced (Liu et al, 2019). Therefore, we proposed the following hypothesis (H4): perceived school climate is also a moderated factor in the mediating (psychological suzhi) first half of pathway.…”
Section: The Moderating Role Of Perceived School Climatementioning
confidence: 97%
“…Previous studies have pointed out that a positive perceived school climate could both protect negative factors and positively promote the development, healthy growth and academic performance of adolescents (Thapa et al, 2013). Positive perceived school climate can improve adolescents' school adjustment and then buffer the negative impact of bullying (Liu et al, 2019). From the perspective of ecosystem theory (Bronfenbrenner, 1989), the positive perceived school climate reflected the harmonious relationship between individuals and various micro-systems to some extent.…”
Section: The Moderated Role Of Perceived School Climatementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that psychological suzhi affects the early behaviour development of adolescents as a mediator. Liu et al (2019) explored the relationship between psychological suzhi, school climate and alcohol use. The results showed that psychological suzhi can effectively predict alcohol use and adolescents with low psychological suzhi are more likely to use alcohol than adolescents with high psychological suzhi.…”
Section: Psychological Suzhimentioning
confidence: 99%
“…Psychological suzhi is a concept local to China and is also the focus of current educational departments. Numerous studies have demonstrated that psychological suzhi is inseparable from the development of children’s behavior [ 8 , 9 , 10 , 11 , 12 ]. However, research on psychological suzhi and prosocial behavior remains limited, especially concerning longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%